A Preliminary Study of Run-off and Soil-wash in Run-off Plots at Jhargram, West Bengal - Ray, Mukul P. (Indian Forester, 1971)
This paper presents the results of the preliminary observations made for five years on run-off and soil-wash with small run-off plots at Jhargram (District Midnapore), West Bengal. Eight plots of 0.03 ha (60 m Ã— 5 m) each were laid out adjacent to one another in a sal coppice forest in 1964. Three plots were under bushy coppice crop of sal with or without trenches, three plots were under tall coppice crop with or without trenches, one plot was under tall coppice crop but was burnt twice annually and one plot was a waste land without vegetation. From the observations so far made it is seen that run-off and soil-wash is highest in a waste land followed by the burnt plot. The bushy coppice plot produced more run-off but less soli-wash as compared with a tall coppice plot. Trenches reduced both the run-off and soil-wash. The study is still in progress. It is expected that more firm results will become available in due course.